Effectiveness of Milrinone in Preventing Myocardial Infarction After Coronary Artery Bypass Graft Surgery - Akram, Muhammad Adnan; Alam, Waqas; Masror, Rehan; Shah, Syed Ali Raza Ali; Naseer, Mehwish; Qureshi, Kamil Hussain (Pakistan Armed Forces Medical Journal, 2025)
Objective: To study the effectiveness of Milrinone in prevention of Myocardial Infarction (MI) after Coronary Artery Bypass Grafting (CABG) surgery. Study Design: Quasi experimental study. Place and Duration of Study: Armed Forces Institute of Cardiology & National Institute of Heart Diseases, Rawalpindi Pakistan, from Jun to Dec 2023. Methodology: One hundred and twenty patients who underwent CABG irrespective of age and gender were enrolled through non probability consecutive sampling. Patients were divided equally into two groups non-randomly: Milrinone-Group (Group- M) and Saline-Group (Group-S). Before coming off bypass in on pump cases and after completion of grafting in off pump cases, bolus dose of Milrinone 50μg/kg was administered in Group- M and same volume of normal Saline in Group-S. The primary endpoint of the study was the occurrence of postoperative myocardial infarction (PMI), as determined by Electrocardiography (ECG) and cardiac biomarkers (CK and CKMB). Results: Out of 120 patients, 106(88.37%) were males and 14(11.60%) were females with median age of 58.00(53.00-68.75) years. In Group-M and Group-S, raised CKMB levels was observed in 7(11.7%) and 20(33.3%) patients respectively (p=0.008). Regarding ECG changes, both groups demonstrated statistically insignificant difference (Group-M: 4(6.7%) patients vs. Group-S: 7(11.7%) patients; p>0.05). Conclusion: Milrinone may have some cardioprotective effects, by lowering CKMB level but it was not consistently effective in prevention of MI following CABG surgery.